2020
DOI: 10.3390/ijms21218103
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Affected MSC Functions and Severity of Periodontal Tissue Destruction in a Ligature-Induced Mouse Periodontitis Model

Abstract: Mesenchymal stem cells (MSCs) are known to play important roles in the repair of lost or damaged tissues and immunotolerance. On the other hand, aging is known to impair MSC function. However, little is currently known about how aged MSCs affect the host response to the local inflammatory condition and tissue deterioration in periodontitis, which is a progressive destructive disease of the periodontal tissue potentially leading to multiple tooth loss. In this study, we examined the relationship between aging-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…Our team also detected that the application of the Wnt signaling antagonist DKK1 led to an increase in osteogenic differentiation in PDLSCs derived from the inflammatory microenvironment (Sun et al, 2017). Earlier studies have found that aging is also a chronic inflammatory process (Zhang et al, 2012;Aung et al, 2020), which implicates similar trends of cells from donors with periodontitis and aged donors. In this study, the results showed that P-GSK-3β and active-β-catenin decreased in the co-culture system, while GSK-3β and total-β-catenin remained unmodified, suggesting the suppression of the Wnt pathway in PDLSCs from an impaired microenvironment after co-cultured with ERM (Figure 6).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our team also detected that the application of the Wnt signaling antagonist DKK1 led to an increase in osteogenic differentiation in PDLSCs derived from the inflammatory microenvironment (Sun et al, 2017). Earlier studies have found that aging is also a chronic inflammatory process (Zhang et al, 2012;Aung et al, 2020), which implicates similar trends of cells from donors with periodontitis and aged donors. In this study, the results showed that P-GSK-3β and active-β-catenin decreased in the co-culture system, while GSK-3β and total-β-catenin remained unmodified, suggesting the suppression of the Wnt pathway in PDLSCs from an impaired microenvironment after co-cultured with ERM (Figure 6).…”
Section: Discussionsupporting
confidence: 51%
“…For instance, the efficacy of periodontal regeneration declines in diabetes compared with healthy animals (Kim et al, 2020;Nguyen et al, 2020). Furthermore, PDLSCs from aged microenvironment exhibited reduced colony-forming ability, proliferative, migratory and osteogenic potential than PDLSCs from healthy PDL (Zheng et al, 2009;Wu et al, 2015;Aung et al, 2020). For PDLSCs isolated from periodontitis, our team previously found that the proliferative capacity of them increased but the osteogenic potential of them was significantly lower than that of PDLSCs isolated from healthy PDL (Liu et al, 2011;Tang et al, 2016;Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study revealed that the expression of surface antigen markers of MSCs (Sca-1, CD90, CD146), colony formation, migration, and osteogenesis of aged MSCs were significantly lower than those of young MSCs. These results suggested that aging-induced impairment of MSC function is potentially correlated with progressive periodontal tissue deterioration [72]. Recently, the ligature-induced bone loss method has been modified for dental implants to investigate peri-implantitis.…”
Section: Othersmentioning
confidence: 99%
“…After the 3-week culture period, the cells were then washed with PBS and stained with 0.1% toluidine blue contained in 1% PFA overnight. On the following day, dishes were washed to remove excess dye, and only stained clusters containing more than 50 cells were counted as colonies [ 28 ].…”
Section: Methodsmentioning
confidence: 99%